PERAN KETERAMPILAN BERBICARA DI DEPAN UMUM DALAM MENINGKATKAN EFEKTIVITAS PRESENTASI AKADEMIK - Rahmadhania, Sabrina Alsya; Marsofiyati; Utari, Eka Dewi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study discusses the role of public speaking skills in encouraging the effectiveness of academic presentations in students of the Faculty of Economics and Business, State University of Jakarta. This research uses a quantitative approach with a survey method. With a total of 50 students who became respondents in this study which was then tested using SPSS software, the results showed that public speaking skills remain an important factor in academic presentations to be effective. Therefore, training and development related to public speaking are needed to encourage the improvement of the quality of student presentations in the academic environment.